Left Ventricular Thrombus as Cause of Acute Ischemia of the Lower Limb and Ischemic Stroke: About A Case Report and A Review of the Literature: A case report and a review of the literature - Serroukh, Youssra; Jalal, Tagueniti; Zakaria, Choho; Pascal, Goube (RA Journal of Applied Research, 2022)
The formation of an intraventricular thrombus (TIV) is a serious complication of acute myocardial infarction. The presence of a thrombus is associated with an increased risk of systemic embolization, risk of around 20% in the presence of a TIV of apical topography. The importance of this risk makes it essential to detect this complication early, so as to initiate adequate anticogulant treatment without delay. We report the case of 50 years old male presented with anterior myocardial infarction with left ventricular dysfonction and apical thrombosis which is complicated by acute ischemia of the lower left limb and ischemic stroke.